Maternal and Adolescent Factors Associated with Menstrual Hygiene of Girls in Senior Secondary Schools in Lagos, Nigeria - Rasheed, Tajudeen Olusegun; Afolabi, Wasiu Adebowale (Journal of Maternal and Child Health, 2021)
Background: